Detection of multiple clones and extended-spectrum β-lactamase production among Klebsiella pneumoniae complex isolates from the milk of cows with different severity scores of clinical mastitis - Rissetti, Rafaela Mastrangelo [UNESP]; de Paula, Carolina Lechinski [UNESP]; Yamada, Amanda Yaeko; de Jesus Bertani, Amanda Maria; Costa, Ana Beatriz Nascimento; Sacchi, Claudio Tavares; Campos, Karoline Rodrigues; Guerra, Simony Trevisan [UNESP]; Guimarães, Felipe Freitas [UNESP]; Joaquim, Sâmea Fernandes [UNESP]; Langoni, Hélio [UNESP]; Rall, Vera Lúcia Mores [UNESP]; et al. (Oxford University Press (OUP), 2025)
This study aimed to evaluate the antimicrobial susceptibility and clonal relatedness of Klebsiella pneumoniae isolates recovered from the milk of cows with mastitis in a large-scale study that clinical severity was scored. A total of 48 K. pneumoniae complex isolates were subjected to in vitro antimicrobial susceptibility tests (AST), PCR for carbapenemase-encoding genes, and molecular typing by pulsed-field gel electrophoresis (PFGE). Thirteen isolates, selected by PFGE type and AST results were subjected to whole-genome sequencing (WGS) for the identification of sequence types (STs) and the detection of antimicrobial resistance genes and virulence-encoding genes. A total of 39 different PFGE restriction profiles were identified. Thirteen different STs, including two novel STs, were identified among the 13 sequenced strains. The blaCTX-M-8, qnrE1, aadA2, cmlA4, dfrA15, sul1, tetA, and tetB genes were identified. Two isolates presented the yersiniabactin-encoding gene ybtAEPQSTUX. Klebsiella pneumoniae isolates from the milk of cows with mastitis clinically scored revealed high genetic diversity, according to both PFGE and MLST analysis, as well as harboring resistance genes commonly found in human clinical isolates.